PENGARUH LATIHAN INTERVAL TRAINING TERHADAP PENINGKATAN DAYA TAHAN ATLET MARCHING BAND SEKOLAH MENENGAH PERTAMA SANTO XAVERIUS 1 KABANJAHE - Hizkia Yogalana Simanjorang; Julius Boy Nesra Basgimata Barus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of interval training on improving cardiorespiratory endurance of marching band athletes at Santo Xaverius 1 Junior High School Kabanjahe. The background of this research is based on the low physical endurance of marching band members, indicated by rapid fatigue during training and performances, as well as the absence of a structured physical training program. This research employed an experimental method using a one-group pre-test and post-test design. The population consisted of all 21 marching band athletes, with a sample of 20 students selected through total sampling. Data were collected using the Beep Test instrument to measure aerobic capacity (VO₂max). The treatment was in the form of High-Intensity Interval Training (HIIT) program for 12 weeks, three times per week, at an intensity of 80–90% of maximum heart rate. Data analysis included descriptive statistics, normality test, homogeneity test, and Paired Sample t-Test. The results showed an average increase in VO₂max from 29.29 to 36.24, with a significance value of 0.000 < 0.05. It can be concluded that interval training has a significant effect on improving the endurance of marching band athletes.